2020
DOI: 10.1016/j.red.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational debt dynamics without tears

Abstract: Governments, motivated by a desire to improve upon long-run laissez faire, routinely undertake enduring, productive expenditures, say, in public education, that generate positive externalities across cohorts but require investments be made up front. If everyone after the policy is initiated is at least as happy as before and there are some outstanding resources, the Hicks-Kaldor efficiency rule suggests that the present value of these resources could, hypothetically, be distributed to future generations creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The level of compensation we derived in our static setting is a first step toward understanding the design of tax changes over the life cycle or over time. Andersen and Bhattacharya (2017, 2020), Andersen, Bhattacharya, and Liu (2020), and, more recently, Dávila and Schaab (2021), who extend the generalized marginal social welfare weights approach of Saez and Stantcheva (2016) to dynamic environments, provide useful steps in these directions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of compensation we derived in our static setting is a first step toward understanding the design of tax changes over the life cycle or over time. Andersen and Bhattacharya (2017, 2020), Andersen, Bhattacharya, and Liu (2020), and, more recently, Dávila and Schaab (2021), who extend the generalized marginal social welfare weights approach of Saez and Stantcheva (2016) to dynamic environments, provide useful steps in these directions.…”
Section: Discussionmentioning
confidence: 99%
“…The generality of the tax reforms, in particular, is necessary to ensure that every agent's welfare is compensated for. Andersen and Bhattacharya (2017, 2020) and Andersen, Bhattacharya, and Liu (2020) extend the Kaldor–Hicks approach to dynamic overlapping generations (OLG) settings; they focus on achieving generation‐by‐generation Pareto neutrality via taxation and debt, and do not consider intra‐generational heterogeneity. More broadly, our model is within the class of Mirrleesian economies in general equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Morimoto et al (2017) assess both sustainability and social welfare in a small open endogenously growing economy and show that expenditure-based consolidation can be preferable for both fiscal sustainability and welfare. 4 However, previous studies on transitional dynamics, optimal paces of fiscal consolidation, and spending-based versus tax-based consolidation assume an infinitely lived agent, and therefore ignore intergenerational welfare losses or gains and the possibility of a Ponzi game by governments. Chalk (2000), de la Croix and Michel (2002), and Yakita (2008) investigate the sustainability of public debt (global transitional dynamics of debt) in OLG models and concluded that a Ponzi game by the governments is possible.…”
Section: Related Literaturementioning
confidence: 99%
“…The value of α in the US: α U S = 0.35, in Greece: α GRE = 0.4, in Italy: α IT A = 0.39, and in Portugal: α P RT = 0.39 follow the values in Trabandt and Uhlig (2011). The average annual population growth rate between 2000 and 2019 was 0.97% in the US, 0.21% in 12 This adjustment between a stock and a flow is in line with Song et al (2012) and Andersen and Bhattacharya (2020). They employ OLG models where one period corresponds to 20 or 30 years.…”
Section: The Us Greece Portugal and Italymentioning
confidence: 99%
See 1 more Smart Citation